Monitoring in the treatment of patients with aneurysmal and nonaneurysmal subarachnoid haemorrhage in terms of nursing care and therapy - Čustović, Mirsada (Array, 2019)
Cerebrovascular diseases together with cardiovascular and malignant diseases are the most common diseases in the developed world, regardless of the gender. They are at the third place as the cause of mortality and first as the cause of disability. Subarachnoid haemorrhage is a condition of discharging blood from cerebral arteries into the subarachnoid space within the brain. Subarachnoid haemorrhage (SAH) has a number of etiological features, but when it comes to spontaneous subarachnoid haemorrhage, in 80% of the cases it is caused by the rupture of an intracranial aneurysm. Subarachnoid haemorrhage (SAH) can be spontaneous and traumatic (post-traumatic). Also, it could be primary (direct bleeding into the subarachnoid space) or secondary (parenchymal bleeding to the subarachnoid space of the brain). Cerebral aneurysms are a local expansion in the blood vessel wall usually at the bifurcation of the artery. If cerebral artery ruptures and blood enters the subarachnoid space, the patient can have a very strong headache at the back and front part of the head. Short term memory can be affected as well. The initial assessment of patients should include: an overview of the quantitative state of mind, pupil size and reaction to light, motor and sensory function, the presence of headaches, dysfunction of cranial nerve (ptosis of the eyelids, difficulty moving eyes in all directions) blurred vision, aphasia, other neurological deficits). Several serious complications often arise after a successful operative treatment of the subarachnoid haemorrhage and aneurysm. One such complication is cerebral vasospasm, and is present in 50 to 70% of the patients. Late complications include recurrent bleeding, brain edema, chronic hydrocephalus and as most important - brain infarction. The incidence of subarachnoid haemorrhage ranges from 10-15/100 000 inhabitants.